Forming Linguistic Competence of Foreign Students at the Preparatory Department of a Technical University; Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Efremova O. N. Oksana Nikolaevna (2015, 2015)
Title screen